Mechanistic insights into connexin-mediated neuroglia crosstalk in neurodegenerative diseases - Denaro, Simona; D’Aprile, Simona; Vicario, Nunzio; Parenti, Rosalba (Frontiers in Cellular Neuroscience, 2025)
Neurodegenerative diseases, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), Multiple Sclerosis (MS), and Huntington’s disease (HD), although distinct in their clinical manifestations, share a common hallmark: a disrupted neuroinflammatory environment orchestrated by dysregulation of neuroglial intercellular communication. Neuroglial crosstalk is physiologically ensured by extracellular mediators and by the activity of connexins (Cxs), the forming proteins of gap junctions (Gjs) and hemichannels (HCs), which maintain intracellular and extracellular homeostasis. However, accumulating evidence suggests that Cxs can also act as pathological pore in neuroinflammatory conditions, thereby contributing to neurodegenerative phenomena such as synaptic dysfunction, oxidative stress, and ultimately cell death. This review explores mechanistic insights of Cxs-mediated intercellular communication in the progression of neurodegenerative diseases and discusses the therapeutic potential of targeting Cxs to restore cellular homeostasis.